Copd assessment test (cat) score of patients with chronic obstructive pulmonary disease based on clinical phenotypes - Ng, Diana Leh-Ching; Chai, Chee Shee; Liam, Chong Kin; Pang, Yong Kek; Tan, Seng Beng (Wiley Online Library, 2018)
Background and Aims: Spanish chronic obstructive pulmonary disease (COPD) guideline classifies COPD into 4 clinical phenotypes: nonexacerbator (A), asthma-COPD overlap (B), exacerbator with emphysema (C) and exacerbator with bronchitis (D).